In vitro antioxidant activity and SPF determination in dermocosmetic formulations containig buriti oil (Mauritia flexuosa L.) (Research, Society and Development, 2022)
The goal of this study was whether dermocosmetic formulations made with artisanally extracted buriti oil (Mauritia flexuosa) exhibit photoprotective action in vitro. Two samples acquired from different producers were tested for this purpose. In vitro studies were performed to evaluate the quality of the oil, as well as the production of creams with varying quantities of buriti oil and the analysis of the Sun Protection Factor using the Mansur methodology. The preliminary stability was assessed in regard to organoleptic properties. During the preliminary stability analysis, only formulations with a concentration of 5% oil remained stable, despite the fact that a sample was rejected because it did not satisfy the ANVISA requirements. According to the SPF analysis, buriti oil has a sun protection factor of 4.9, which means that when added to formulations that already contain sunscreen, the oil improves and potentiates the SPF of the formulation.